Refer to the image attached.
Since, we have to divide the polynomial
by (x+2) using synthetic division.
We will divide the coefficients 4 -2 3 by -2
First term = 4 will remain same.
Second term =
![(-2 * 4) -2 = -8-2 = -10](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8w6mndpec9p19ubwlowuavk6aslcoowd0j.png)
So, second term = -10
Third term =
![(-2 * -10)+3 = 23](https://img.qammunity.org/2019/formulas/mathematics/middle-school/lz3g59jxmtqxhq708pwmuc0uah6pb1l8ri.png)
So, third term = 23
So, 4 -10 23 is the correct answer
So, Option 2 is the correct answer.